2018
DOI: 10.1111/emre.12320
|View full text |Cite
|
Sign up to set email alerts
|

Organizational Learning of Absorptive Capacity and Innovation: Does Leadership Matter?

Abstract: Following the process-based definition of absorptive capacity, this study seeks to explore the mediating role of transformational and transactional leadership styles in the relationship between the three learning processes of absorptive capacity and innovation. Based on a survey in the United Arab Emirates (UAE), it was found that transformational leadership mediates the relationship between exploratory and transformational learning processes and innovation. It was also found that transactional leadership did … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
43
1
4

Year Published

2020
2020
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 162 publications
(264 reference statements)
2
43
1
4
Order By: Relevance
“…The influence of leaders on their development has also been explored by many scholars. Darwish et al (2020) found that transformational leadership can adjust the relationship between exploratory and transformational learning processes and innovation based on the investigation and analysis in the United Arab Emirates and enhance enterprise learning. Ricardianto et al (2020) used sampling techniques to analyze the influence of leadership style, work-life balance, and employee engagement on the work efficiency of 290 crew members.…”
Section: Literature Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…The influence of leaders on their development has also been explored by many scholars. Darwish et al (2020) found that transformational leadership can adjust the relationship between exploratory and transformational learning processes and innovation based on the investigation and analysis in the United Arab Emirates and enhance enterprise learning. Ricardianto et al (2020) used sampling techniques to analyze the influence of leadership style, work-life balance, and employee engagement on the work efficiency of 290 crew members.…”
Section: Literature Reviewmentioning
confidence: 99%
“…Entrepreneurship is a process in which entrepreneurs optimize and integrate their own resources or make efforts to create greater economic or social value. It can not only realize self-employment and complete individual ideas but also play an important role in economic development and the expansion of social work positions ( Laguía et al, 2019 ; Saebi et al, 2019 ; Darwish et al, 2020 ). Organizational performance refers to the quantity, quality, efficiency, and profitability of organizational tasks completed in a certain period of time, which is the core issue of strategic management research, and how to effectively improve organizational performance is naturally the most concerned issue for entrepreneurs ( Guterresa et al, 2020 ).…”
Section: Introductionmentioning
confidence: 99%
“…Research recognizes that emerging market firms have relatively underdeveloped absorptive capacity (Bilgili, Kedia, & Bilgili, 2016; Darwish, Zeng, Rezaei Zadeh, & Haak‐Saheem, 2019). Yet scant attention has been paid to the conditions that constrain or facilitate firms' absorptive capacity development within emerging market economies.…”
Section: Introductionmentioning
confidence: 99%
“…Although there is a burgeoning body of literature on absorptive capacity and how it can enhance organizational performance (Zahra & George, 2002; Todorova & Durisin, 2007; Volberda, Foss, & Lyles, 2010), the role of intraorganizational factors remains relatively underinvestigated (Flatten, Adams, & Brettel, 2015; Vera & Crossan, 2004). From this perspective, leadership constitutes a particularly important internal dimension (Nonaka & Takeuchi, 1995; Darwish et al, 2019). Existing research indicates that leadership is the core of organizational activities, influencing the development of organizational capabilities and learning processes (Singh, 2008; Aragón‐Correa, García‐Morales, & Cordón‐Pozo, 2007; Pablo, Reay, Dewald, & Casebeer, 2007), and leadership is critical to enabling and sustaining of capabilities such as absorptive capacity (Berson, Nemanich, Waldman, Galvin, & Keller, 2006; Teece, 2007).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation